MENINGKATKAN HASIL BELAJAR SISWA KELAS VII BMTs NURUL FALAH PALUPADA MATERI UNTUNG DAN RUGI MELALUI PENERAPAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION (RME): Improving Student Learning Outcomes Of Class Viib Mts Nurul Falah Palu On Profit And Loss Material Through The Application Of The Realistic Approach Mathematic Education (Rme) - Istiqomah; Rochaminah, Sutji; Hasbi, Muh. (Universitas Tadulako, 2024)
This research intends to describe the application of the Realistic Mathematic Education (RME) approach to profit and loss material of the VII B grade at MTs Nurul Falah Palu. This type of classroom action research (PTK). Design used in this classroom action research was Arikunto’s that consisted of planning, action, observation, and reflection. The Subject of this research were 20 students of class VII B MTs Nurul Falah Palu. This research was conducted in two cycles. The results showed that in the final test cycle I there were 11 students who completed and 9 students did not complete with a percentage of classical learning completeness reaching 55%, while in cycle II there were 16 students completing and 4 students not completing with a classical learning completeness percentage reaching 80%. The observation results in cycle I showed that the activities of teachers and student groups were in the good category, while in the second cycle the activities of teachers and student groups were in the very good category. The results of this study indicate that the application of the Realistic Mathematic Education learning approach can improve student learning outcomes on the profit and loss material of class VII B grade at MTs Nurul Falah Palu through the following steps:1) understanding the contextual problems, in this stage the teacher presented contextual problems in LKPD and students discuss in their groups to understand the problems given by the teacher, 2) Explaining the problem, the teacher provides help if its needed in the form of questions that can direct students to solve problems 3) solving the problem, students in each group work together to solve the problems through following working steps of LKPD 4) comparing, and discussing the answer, each of group representative presents their answer in order from problem solving and the other member of group compare the answer they have to answer presented by the other group, 5) concluding, teacher guided students to conclude material they just learn. The props used are play money.